2017
DOI: 10.1097/qad.0000000000001606
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early mortality on antiretroviral therapy in advanced HIV-infected adults

Abstract: Summary Background Many HIV-infected individuals present with advanced HIV disease. These patients are at high risk of death after antiretroviral therapy (ART) initiation, but risk factors for death in these patients are unclear. Methods We used data from a multi-site randomized trial comparing empiric versus preventive TB therapy in HIV-infected adults initiating ART with CD4 counts <50 cells/mm3 to evaluate risk factors for death within 48 weeks after ART initiation. Cox proportional hazards models were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 26 publications
6
37
0
1
Order By: Relevance
“…The second study from South Africa further highlights a relatively new understanding, that an increasing proportion of people with very advanced HIV disease are ART experienced, and in this study increased from 14.3% in 2008 to 56.7% in 2017 [ 2 ]. Again, men were at greater risk [ 2 ], a finding reported by other studies [ 4 , 5 ]. These findings are supported by a study from Kenya and the Democratic Republic of Congo (DRC) using data from inpatient departments in Médecins Sans Frontières–supported hospital wards [ 3 ], which found that the majority of HIV-infected hospitalized patients in both sites were ART experienced.…”
mentioning
confidence: 68%
“…The second study from South Africa further highlights a relatively new understanding, that an increasing proportion of people with very advanced HIV disease are ART experienced, and in this study increased from 14.3% in 2008 to 56.7% in 2017 [ 2 ]. Again, men were at greater risk [ 2 ], a finding reported by other studies [ 4 , 5 ]. These findings are supported by a study from Kenya and the Democratic Republic of Congo (DRC) using data from inpatient departments in Médecins Sans Frontières–supported hospital wards [ 3 ], which found that the majority of HIV-infected hospitalized patients in both sites were ART experienced.…”
mentioning
confidence: 68%
“…We compared the cascade of care (from diagnosis (those who knew they were HIV-positive), to those on ART, to virologically suppressed) for all individuals with advanced HIV disease stratified by country and sex using chi-square tests. As the risk of mortality and morbidity increases with decreasing CD4 cell count [4][5][6], we also evaluated the cascade of care only among individuals with CD4 < 100 cells/µl. Among those on ART, we further examined the distribution of advanced HIV by duration on ART, categorized as <6 months or ≥6 months on ART.…”
Section: Statistical Methods and Analysismentioning
confidence: 99%
“…About 940,000 HIV-related deaths occurred globally in 2017 and about 70% of these were from sub-Saharan Africa [3]. Mortality is very high among individuals with advanced HIV disease particularly those with very low CD4 count [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of 850 HIV-infected adults/adolescents initiating ART with CD4 count <50 cells/µL, randomized to receive empiric tuberculosis treatment or isoniazid preventive therapy, identified higher mortality in those with lower CD4 cell count, albumin, and hemoglobin; higher white blood cell (WBC) count or neutrophil percentage; or lymphadenopathy [ 10 ]. Given the substantial numbers presenting with low CD4 cell count and their high mortality shortly after ART initiation, additional studies in “late presenters” are important to identify their key characteristics, particularly if baseline CD4 count testing is not always available, to identify them earlier at healthcare facilities and prioritize them for additional interventions.…”
mentioning
confidence: 99%